Two porous-layered borates built by B7O13(OH) clusters and AlO4/GaO4 tetrahedra. Issue 45 (9th November 2022) - Dong, Ya-Zhuo; Chen, Chong-An; Chen, Juan; Cheng, Jian-Wen; Li, Jin-Hua; Yang, Guo-Yu
Abstract : A three-dimensional porous-layered aluminoborate and galloborate have been obtained under solvothermal conditions, which are built by B7 O13 (OH) clusters and AlO4 /GaO4 units, respectively. Abstract : Two three-dimensional (3D) porous-layered borates, Na0.5 K2.5 [AlB7 O13 (OH)]·H2 O (1 ) and NaKCs[GaB7 O13 (OH)]·1.5H2 O (2 ), have been obtained under solvothermal conditions. Compound 1 crystallizes in the triclinic space group P 1̄, while 2 crystallizes in the monoclinic space group P 21 / n . Compounds 1 and 2 contain similar units of B7 O13 (OH) and AlO4 /GaO4 ; the strict alternations of B7 O13 (OH) clusters and AlO4 /GaO4 resulted in 3D open-framework layers with 8-R and 13-R channels along different directions. The shapes and orientations of the channels of 1 and 2 are different due to their different space groups. It's interesting to note that three different alkali metal ions (Na +, K +, and Cs + ) are found in different positions in 2 . UV-vis diffuse reflectance analysis indicates that both compounds show a wide transparency range with a short-wavelength absorption edge below 190 nm.